Cognitive Appraisal as a Mediating Effect between Stress Coping Strategies towards Adaptation to Stress and Psychological Well Being among Chinese University Teachers - Xiaoli, Zhao; Veloo, Arsaythamby (South Asian Journal of Social Sciences and Humanities, 2024)
Background: The job of university teachers often brings intensive and challenging situations  and the demands of such a working environment requires the teachers to rely on various  stress coping mechanism to face these challenging situations. Therefore, the present study  evaluates the extent to which cognitive appraisal mediates the correlation between the stress coping strategies of these teachers and their impact on their psychological well-being. The  present study explores the mediating effect of cognitive appraisal between stress-coping  strategies towards adaptation to stress and psychological well-being among Chinese  university teachers.  Methods: The present study focuses on the population of university teachers in China and  collected data through a survey questionnaire. The questionnaire is designed using items from  the literature. Findings: The results indicated positive and significant impacts of co-regulation and self regulation on psychological well-being and adaptation to stress. In addition, the study  supported the mediating role of coping potential and threat perception.  Conclusion and Implications: The study provided insights into how both individual and  interpersonal factors contribute to enhancing stress adaptation and psychological health of  university teachers and adds value to the existing literature. In addition, the practical  implications of the study recommend effective strategies for enhancing the well-being of  teachers. Policymakers and educational institutions can benefit from the findings to foster  positive work environments and support the psychological well-being of teachers.
Keywords: Cognitive appraisal; Stress-coping strategies; Adaptation to stress; Psychological well-being